Application of Management Accounting in Micro Small and Medium Enterprises (MSMEs): Hawalom Kupi Ulee Kareng Lhokseumawe City - Muhammad Randa Siregar; Muammar Khadafi; Muhammad Mirza Ananda; Nurrahmi Nurrahmi; Alma Agnar (LPPM UIKA Bogor, 2024)
This research looks at how management accounting functions and factors are implemented. Hawalom Kupi Ulee Kareng, Lhokseumawe City is the object of research. Primary and secondary data were used in this research. This research uses qualitative methods using interactive analysis. Data obtained directly from the owner of Hawalom Kupi Ulee Kareng Lhokseumawe and data analysis in the field so that it is more representative. Data collection techniques are used to collect data seen from its use through observation and so on. Data must provide information based on supporting facts, including by conducting (1) Interviews, (2) Observations. Interviews were asked to the owner of the research object in the form of unstructured questions. Observations are carried out directly so as to obtain relevant results, and can also be used as a reference. The results of observations and interviews are presented in table form with a clear explanation of the research objects in implementing the functions of implementing management accounting, namely planning, organizing, directing, controlling and decision making.